Cross-cultural adaptation and validation of the Danish consensus version of the 10-item Perceived Stress Scale - Anita Eskildsen; Vita Ligaya Dalgaard; Kent Jacob Nielsen; Johan H Andersen; Robert Zachariae; Lis Raabæk Olsen; Anders Jørgensen; David Høyrup Christiansen (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: The aims of the present study were to (i) cross-culturally adapt a Danish consensus version of the 10-item Perceived Stress Scale (PSS-10) and (ii) evaluate its psychometric properties in terms of agreement, reliability, validity, responsiveness, and interpretability among patients with work-related stress complaints. METHODS: A consensus-building process was performed involving the authors of the three previous Danish translations and the consensus version was back-translated into English and pilot-tested. Psychometric properties of the final version were examined in a sample of 64 patients with work-related stress complaints. RESULTS: The face validity, reliability, and internal consistency of the Danish consensus version of the PSS-10 were satisfactory, and convergent construct validity was confirmed. Receiver operating characteristic (ROC) curves of the change scores showed that the ability of the PSS-10 to correctly classify patients as improved or unchanged according to the patients' own judgment was acceptable. The estimates of minimal clinically important change were 11 points and 28% for absolute and relative change scores, respectively. CONCLUSION: The Danish consensus version of the PSS-10 appears to be feasible for use in clinical research settings and has good psychometric properties in terms of agreement, reliability, validity, responsiveness, and interpretability.